Aggregated, Conformationally Changed Fibrinogen Exposes the Stimulating Sites for t-PA-Catalysed Plasminogen Activation - Haddeland, Unni; Sletten, Knut; Bennick, Anne; Nieuwenhuizen, Willem; Brosstad, Frank (Thrombosis and Haemostasis, 1996)
The present paper shows that conformationally changed fibrinogen can expose the sites Aα-(148-160) and γ-(312-324) involved in stimulation of the tissue-type plasminogen activator (t-PA)-catalysed plasminogen activation. The exposure of the stimulating sites was determined by ELISA using mABs directed to these sites, and was shown to coincide with stimulation of t-PA-catalysed plasminogen activation as assessed in an assay using a chromogenic substrate for plasmin. Gel permeation chromatography of fibrinogen conformationally changed by heat (46.5° C for 25 min) demonstrated the presence of both aggregated and monomeric fibrinogen. The aggregated fibrinogen, but not the monomeric fibrinogen, had exposed the epitopes Aα-(148-160) and γ-(312-324) involved in t-PA-stimulation. Fibrinogen subjected to heat in the presence of 3 mM of the tetrapeptide GPRP neither aggregates nor exposes the rate-enhancing sites. Thus, aggregation and exposure of t-PA-stimulating sites in fibrinogen seem to be related phenomena, and it is tempting to believe that the exposure of stimulating sites is a consequence of the conformational changes that occur during aggregation, or self-association. Fibrin monomers kept in a monomeric state by a final GPRP concentration of 3 mM do not expose the epitopes Aα-(148-160) and γ-(312-324) involved in t-PA-stimulation, whereas dilution of GPRP to a concentration that is no longer anti-polymerizing, results in exposure of these sites. Consequently, the exposure of t-PA-stimulating sites in fibrin as well is due to the conformational changes that occur during selfassociation.